Heritability and genome-wide association study of diffusing capacity of the lung. Issue 3 (15th September 2018) - Terzikhan, Natalie; Sun, Fangui; Verhamme, Fien M.; Adams, Hieab H.H.; Loth, Daan; Bracke, Ken R.; Stricker, Bruno H.C.; Lahousse, Lies; Dupuis, Josée; Brusselle, Guy G.; O'Connor, George T.
Although several genome-wide association studies (GWAS) have investigated the genetics of pulmonary ventilatory function, little is known about the genetic factors that influence gas exchange. The aim of the study was to investigate the heritability of, and genetic variants associated with the diffusing capacity of the lung. GWAS was performed on diffusing capacity of the lung measured by carbon monoxide uptake ( D LCO ) and per alveolar volume ( V A ) using the single-breath technique, in 8372 individuals from two population-based cohort studies, the Rotterdam Study and the Framingham Heart Study. Heritability was estimated in related (n=6246) and unrelated (n=3286) individuals. Heritability of D LCO and D LCO / V A ranged between 23% and 28% in unrelated individuals and between 45% and 49% in related individuals. Meta-analysis identified a genetic variant in ADGRG6 that is significantly associated with D LCO / V A . Gene expression analysis of ADGRG6 in human lung tissue revealed a decreased expression in patients with chronic obstructive pulmonary disease (COPD) and subjects with decreased D LCO / V A . D LCO and D LCO / V A are heritable traits, with a considerable proportion of variance explained by genetics. A functional variant in ADGRG6 gene region was significantly associated with D LCO / V A . Pulmonary ADGRG6 expression was decreased in patients with COPD. This is the first population-based heritability and GWAS study of gas exchange. We identified a functional variant in ADGRG6, and demonstrated differential expression in lung tissue of patients with COPD and decreased diffusing capacity. http://ow.ly/Rvy430kHIT4